KARAKTERISTIK MOROMI DAN KECAP MANIS SERTA KAJIAN AKTIVITAS ANTIOKSIDANNYA - Rosida, Dedin F; CH, Wijaya; A, Apriyantono; FR, Zakaria (REKAPANGAN, 2010)
Antioxidants are compounds that can retard oxidation in food. Antioxidants should beÂ able Â to Â delay Â or Â prevent Â the Â occurrence Â of Â autooksidasi Â reaction Â of Â free Â radicals Â in Â lipid.Â Compounds that act as antioxidants in moromi and soy sauce Â is mainly caused by the MaillardÂ reaction Â product Â compounds. Â Protein, Â alpha-acids Â and Â phenols Â compound Â that Â can Â beÂ potentially as an antioxidant, in this study havenât showed antioxidant activity. In the soysauceÂ products Â has Â the Â ability Â capture Â the Â DPPH Â radical Â more Â strongly Â on Â the Â fraction Â withÂ molecular Â weight Â 30 Â kDa Â to Â greater Â than Â 100 Â kDa Â and Â its Â activity Â similar Â to Â vitamin Â C Â 200Â ppm, whereas the inhibition of fatty acid oxidation was stronger in the fraction with molecularÂ weight <10 kDa to 30 kDa and its activity is greater than 200 ppm BHT.Key Words : Maillard Reactions,moromi, soysauce, antioxidative activity